2009
DOI: 10.1002/j.0022-0337.2009.73.9.tb04792.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental School Patients with Limited English Proficiency: The California Experience

Abstract: California is home to one-third of the U.S. population with limited English proficiency (LEP). Studies indicate that treating LEP patients without professional interpreters can result in miscommunication, decreased patient satisfaction, and serious medical errors. To address this problem, federal laws require all health care institutions receiving federal monies to provide interpretation services to their LEP patients at no cost to the patient. In this study we surveyed 122 students and fifty-six faculty membe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…Beyond formal curricula, the majority of respondents (84.8%) in our study indicated that their students had access to formal interpreter services to communicate with their LEP patients while in clinic. This finding is in contrast to a 2009 survey of California dental schools, in which only ad hoc interpreters were reported to be in use 15 *. Use of interpreters improves LEP patients’ satisfaction with their care and their health outcomes, although this practice has not been studied in the dental setting 5 * , 35 *.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Beyond formal curricula, the majority of respondents (84.8%) in our study indicated that their students had access to formal interpreter services to communicate with their LEP patients while in clinic. This finding is in contrast to a 2009 survey of California dental schools, in which only ad hoc interpreters were reported to be in use 15 *. Use of interpreters improves LEP patients’ satisfaction with their care and their health outcomes, although this practice has not been studied in the dental setting 5 * , 35 *.…”
Section: Discussionmentioning
confidence: 59%
“…The respondents to our survey estimated that the percentage of LEP patients seen in their dental school clinics was 22.4%, suggesting this level may be nearly three times the national average. The demographics of patients seen at dental school clinics have not been well described in the literature, but a survey of California dental students found that 10–20% of their patients required an interpreter 14 * , 15 *. Given these high rates of LEP patients, curricular competencies pertaining to these populations are critical for appropriate patient care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dental school clinics are a distinctive health care setting in which patients receive affordable dental services from students supervised by licensed dentists. These clinics often attract a greater proportion of patients from underserved populations, including patients with LEP 17 . Trainees who have experience caring for the underserved while in dental school have been found to be more likely to express interest in doing so when they enter practice 18 , 19 .…”
mentioning
confidence: 99%
“…This suggests that changes in the current DSC environment or the process of obtaining care at a DSC may make dental care in this setting more accessible for these groups. The Harvard School of Dental Medicine has no formal interpreter services available for LEP patients, and this situation is consistent with the presence of less-than-ideal interpretation practices previously documented to occur in many DSCs in the US [25,33]. Patient satisfaction has been shown to be higher when professional interpreter services are made available, with satisfaction equally high when telephone interpreter services are used as when in-person interpreters are present [34].…”
Section: Discussionmentioning
confidence: 56%